2020
DOI: 10.3390/plants9020220
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Application Improves Salt Tolerance of Alfalfa (Medicago sativa L.) by Enhancing Antioxidant Capacity

Abstract: Alfalfa (Medicago sativa L.) is an important and widely cultivated forage grass. The productivity and forage quality of alfalfa are severely affected by salt stress. Melatonin is a bioactive molecule with versatile physiological functions and plays important roles in response to various biotic and abiotic stresses. Melatonin has been proven efficient in improving alfalfa drought and waterlogging tolerance in recent studies. In our reports, we applied melatonin exogenously to explore the effects of melatonin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Medicago sativa 250 mM NaCl; 2 w Melatonin increased the activities of CAT, POX, and Cu/Zn-SOD. [210] Cucumis sativus 150 mM NaCl; 3 d Melatonin increased CAT, SOD, POD, and APX by 23%, 29%, 15%, and 16%, respectively.…”
Section: Antioxidant Defense In Plants Under Floodingmentioning
confidence: 95%
“…Medicago sativa 250 mM NaCl; 2 w Melatonin increased the activities of CAT, POX, and Cu/Zn-SOD. [210] Cucumis sativus 150 mM NaCl; 3 d Melatonin increased CAT, SOD, POD, and APX by 23%, 29%, 15%, and 16%, respectively.…”
Section: Antioxidant Defense In Plants Under Floodingmentioning
confidence: 95%
“…results, previous studies revealed that the exogenous application of melatonin can improve morphological responses under drought stress in different plants such as tobacco [12], Camellia sinensis [13], cucumber [14], soybean [15], alfalfa [16], rice [17], maize [18], cotton [19], grape [20], and kiwi [21]. It seems that melatonin as a novel plant growth regulator, independently of auxin signaling, plays a pivotal role in shoot and root growth and development [10,11].…”
Section: Plos Onementioning
confidence: 95%
“…Therefore, it is necessary to apply exogenous melatonin for coping adverse environmental conditions because, sometimes, the endogenous level of melatonin is insufficient for this aim. Several studies have shown that the application of exogenous melatonin could significantly improve stress tolerance in different plants such as tobacco [12], Camellia sinensis [13], cucumber [14], soybean [15], alfalfa [16], rice [17], maize [18], cotton [19], grape [20], and kiwi [21]. Therefore, applying melatonin can be considered as a short-term and promising approach for alleviating drought stress in various economically important plants such as citrus.…”
Section: Introductionmentioning
confidence: 99%
“…Under salt stress, the unsaturated fatty acids of plant membranes are decomposed to malondialdehyde (MDA), and the rate of lipid peroxidation in terms of MDA can be used as a biochemical indicator to evaluate salt-tolerant cultivars [30,64]. The salt tolerance of alfalfa is also improved by melatonin application, which acts as an antioxidant in scavenging H 2 O 2 and enhances antioxidant enzymes' activities [65]. Under salt stress, tolerant alfalfa shows less severe cell membrane damage and lower accumulation of reactive oxygen species (ROS) than salt sensitive types [66].…”
Section: Effect Of Salt Stress On Oxidative Stress and Anti-oxidativementioning
confidence: 99%